Modified endoscopic transnasal‐transmaxillary‐transpterygoid approach to parapharyngeal space tumor resection. Issue 6 (8th February 2016) - Wasano, Koichiro; Yamamoto, Sayuri; Tomisato, Shuta; Kawasaki, Taiji; Ogawa, Kaoru
ABSTRACT: Background: Conventional approaches for removing parapharyngeal space tumors require a cervical skin incision and resection of soft tissues between the skin and parapharyngeal space. The surgical visual field for this conventional approach is limited. Methods: To decrease invasiveness during removal of benign parapharyngeal space tumors and to enhance the visual field, we devised a new approach called the modified endoscopic transnasal‐transmaxillary‐transpterygoid approach (MENMAP). The "surgical corridor" to the parapharyngeal space consists of the maxillary sinus, submucous tunnel under the lateral nasal wall, and the space created by removing the pterygoid process. Results: We successfully performed en bloc removal of a parapharyngeal space tumor using the MENMAP approach. The only surgical complication was hypoesthesia of the right hard palate and maxillary gingiva, which gradually improved. Conclusion: The MENMAP approach is a viable alternative for removing parapharyngeal space tumors, as it is safe, feasible, and less invasive. © 2016 Wiley Periodicals, Inc. Head Neck 38: 933–938, 2016